EFEKTIVITAS PESAN IKLAN "PESANLAH DARI MCDONALDS" DALAM MENYAMPAIKAN PESAN KEPADA PENGIKUT AKUN INSTAGRAM @BURGERKING.ID - Arya Yudha Prakoso (2022)
Marketing Communication or which can be expressed as an activity in communication that has the aim of conveying a message to consumers through various media, with the aim that the communication carried out can produce three stages of change, namely changes in knowledge, changes in attitudes. and changes in actions taken. desired. The advertising message is what the company plans to convey in an advertisement and how the company plans to convey the message verbally and nonverbally. The advertising message must be understood by the target audience so that the advertisement is effective and can achieve its goals. The effectiveness of an advertisement must be measured properly and correctly. Advertising effectiveness is a condition of the extent to which the effect of the advertising message conveyed can attract attention, be understood, understood, arouse emotions and move the target to provide the desired response. This study focuses on how effective the advertising "Order from McDonalds is in conveying messages to Instagram followers @burgerking.id. Instagram as a social media that has a big influence is certainly used by companies that want to display their product advertisements. Burger King is one of the companies that displays ads on Instagram. Burger King's advertising concept "Order from McDonalds" is a unique concept that is rarely carried out by a company. When this ad was posted on Instagram @burgerking.id, of course, burger king received a lot of responses regarding his courage to post an ad that supports its competitors. This advertising concept has never been used by Burger King and its competitors in Indonesia. Therefore, this ad is an ad that is quite unique so it deserves to be researched. This study uses a descriptive quantitative research method where sampling or data collection from Instagram followers @burgerking.id which are taken randomly will produce results from this research. The result of this research is that all elements of the statement tested with descriptive quantitative are declared effective. Keywords: Messages, Advertising, Effectiveness, Marketing Communications, Instagram.